2009
DOI: 10.1897/08-546.1
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic toxicity of sertraline to Pimephales promelas at environmentally relevant surface water pH

Abstract: Abstract-Researchers recognize that ionization state may influence the biological activity of weak acids and bases. Dissociation in aqueous solutions is controlled by the pK a of a compound and the pH of the matrix. Because many pharmaceuticals are implicitly designed as ionizable compounds, site-specific variability in pH of receiving waters may introduce uncertainty to ecological risk assessments. The present study employed 48-h and 7-d toxicity tests with Pimephales promelas exposed to the model weak base p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
100
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 42 publications
(68 reference statements)
10
100
1
1
Order By: Relevance
“…Valenti et al (2009) reported similar toxicity-pH observations with juvenile fathead minnows exposed to sertraline. Further, Valenti et al (2009) performed a time-to-death fathead minnow study with 500 Ilg/L of sertraline, and estimated associated LT50 values of >48,31.9, and 4.9 h at pH treatment levels of 6.5, 7.5, and 8.5, respectively.…”
Section: Site-specific Ph and Api Pkasupporting
confidence: 63%
See 1 more Smart Citation
“…Valenti et al (2009) reported similar toxicity-pH observations with juvenile fathead minnows exposed to sertraline. Further, Valenti et al (2009) performed a time-to-death fathead minnow study with 500 Ilg/L of sertraline, and estimated associated LT50 values of >48,31.9, and 4.9 h at pH treatment levels of 6.5, 7.5, and 8.5, respectively.…”
Section: Site-specific Ph and Api Pkasupporting
confidence: 63%
“…Valenti et al (2009) reported similar toxicity-pH observations with juvenile fathead minnows exposed to sertraline. Further, Valenti et al (2009) performed a time-to-death fathead minnow study with 500 Ilg/L of sertraline, and estimated associated LT50 values of >48,31.9, and 4.9 h at pH treatment levels of 6.5, 7.5, and 8.5, respectively. Such observations support the findings of Nakamura et al (2008) because if more non ionized sertraline exists at higher pH treatment levels, then sertraline should be more bioavailable and more readily absorbed by juvenile fathead minnows, resulting in the observed more rapid onset of mortality at increasingly higher pHs.…”
Section: Site-specific Ph and Api Pkasupporting
confidence: 63%
“…The uptake rate of ionized compounds is lower than that of neutral compounds [11][12][13], although ionized molecules may also be absorbed by ion carriers [13]. In fish, as in humans, a mixed variety of anionic, cationic, and neutral transporters affects the active or passive uptake and elimination of xenobiotics [29].…”
Section: Uptake From Water To Bloodmentioning
confidence: 99%
“…Ionization usually decreases the uptake, bioconcentration, and toxicity of acidic and basic chemicals because of the loss of pure lipophilic characteristics [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, uptake and elimination of ionizable pharmaceuticals (over 70% of drugs are ionizable) by fish [12,13] and invertebrates [14] are modified by surface water pH [13,[15][16][17]. Unfortunately, environmental modelling approaches for predicting fate, transport, exposure and bioaccumulation, which were designed to address historical contaminants (e.g.…”
Section: Introductionmentioning
confidence: 99%